Abundância e distribuição das larvas de peixes no Lago Catalão e no encontro dos rios Solimões e Negro, Amazonas, Brasil - Leite, Rosseval Galdino; Silva, José Vagner Valente da; Carvalho, Carlos Edwar Freitas de (Acta Amazonica, 2006)
The abundance and monthly distribution of fish larvae in Catalão Lake, situated near the confluence of the Solimões and Negro River was evaluated between January and May 2001. The samples were obtained using a conical plankton net (350 µm, Ø 0.3, 2 m long), with a flow meter attached to the opening of the net. The categorical variables were: position in the lake (margin and center), period of the day (day and night) and depth (surface and bottom). The analysis was made with Fatorial Correspondence Analyses (FCA) using the larval density (larvae.m-3) as answer variable and the months as descriptors. The feeding activity of larvae was also studied. Most of them were protolarvae feeding in the margin of the lake, on the surface as well as on the bottom. These results indicated that Catalão Lake is an important nursery ground for to the larvae of fishes that spawn in the Solimões River.
Abundance and distribution of fish larvae in Catalão Lake and in the confluence of the Solimões and Negro River, Amazon, Brazil
Keywords: Solimoes River; Catalão Lake; Fish Larvae; Abundance; Distribution; Feeding; Rio Solimões; Lago Catalão; Larvas De Peixes; Abundância; Distribuição; Alimentação